A Mini Review on the Application of Chitosan Composites for the Adsorption of Fluoride from Aqueous Solution - Sutherland, Clint; Chittoo, Beverly; Islam, Abdel (Current Biotechnology, 2023)
Background: Exploration into the development of cost-effective and eco-friendly adsorbents for the removal of fluoride continues to be unabated. The modification of chitosan through the development of composites and derivatives has shown great promise over the past decade. These modifications aim to overcome the limitation of chitosan, such as separability and adsorption capacity.Objectives: The objective of this study is to review various modifications to chitosan for defluoridation, the resulting adsorption capacities, operational parameters that appreciably influence the fullscale application of adsorption systems and, where reported, the mechanisms that influenced the adsorption process.Results and Discussion: Among the adsorbents reviewed, most of the processes were best modelled by the Langmuir isotherm and the pseudo-second order model. Chitosan composites were able to achieve significantly higher F- adsorption capacities and compared well to other adsorbents in the literature. Gamma degraded chitosan-Fe(III) beads, 10%-Lanthanum-incorporated chitosan beads and neodymium-modified chitosan were found to easily achieve the WHO drinking water limit of 1.5 mg/L. In all instances, the reactions were spontaneous and endothermic. Fluoride adsorption was shown to increase from the acidic region to near neutral pH followed by a decrease into the alkaline range.Conclusion: The presence of competing ions is a major operational parameter for full-scale adsorption applications. The presence of carbonate and bicarbonate ions has been a consistent hindrance in reported studies. Thus, future investigations are warranted in this area.
Keywords: kinetics